The impact of "Think Ink Pair Share" Strategy on developing the writing skills in the Arabic language of the 10th grade students in Jordan - Abu Ajameia, Jehad Khader (Journal of Educational and Psychological Sciences, 2019)
The purpose of this study was inquiring The impact of "Think Pair Share" Strategy on developing the writing  skills in the Arabic language of the 10th grade students in Jordan. To achieve goals of this study, a test has been developed to observe the Development of writing skill. The researcher adopted a quasi- experimental approach in which the experimental group consisting of (30) students was taught in accordance with "Think Pair Share" Strategy. At the same time, the controlled group consisting of (30 students) was taught in the traditional way.The tests and the motive measuring was applied prior and post- teaching on both groups. The Analysis of Covariance results (ANCOVA Test) indicated a significant difference at (α≤0.05) between the two groups, which is attributed to the "Think Pair Share" Strategy, in developing the writing skill, of Learning arabic language Course for the experimental group. The results also indicated variation in the performance of (the experimental group) students in the "Think Pair Share" Strategy on developing the writing skills (in developing the Academic achievement.The study recommended introducing the "Think Pair Share" Strategy in the teaching of Arabic language Course, and conducting other similar studies in different educational stages.
Keywords: strategy; strategy (think, pair, share); think; pair; share; writing skill